The post-black and post-white church : becoming the beloved community in a multi-ethnic world - Smith, Efrem (Efrem D.), 1969- (San Francisco : Jossey-Bass, 2012)
"A blueprint for missional, multi-ethnic Christian communityEfrem Smith, an internationally recognized and innovative African-American leader, offers a workable plan for connecting theology, practical ministry models, and real stories of people in multi-ethnic Christian communities. Using the example of Jesus, Smith develops a theology of multi-ethnic and missional leadership. Embracing urban and ethnic subcultures such as hip-hop, this book provides a rich mix of multi-ethnic church development, reconciliation theology, missional church thinking, and Christian community. Provides a common-sense approach to creating a multi-ethnic Christian community Includes practical ministry models and real stories of people who are members of thriving multi-ethnic congregations Author is acclaimed African-American thought leader who planted and led a multi-ethnic churches of close to 1,000 and now leads a regional division of a denominational committed to ethnic, multi-ethnic, and missional churches This book is written for anyone wrestling with what it means to be a Christian in an increasingly multi-ethnic world polarized by class, politics, and race"--
Reconciling, multi-ethnic, and missional -- Moving the church beyond crisis, captivity, and comfort -- Compassion, mercy, and justice -- Race -- The gift of the black church -- Creating a post-white church -- Leadership -- The beloved life and leadership project -- Starting, shifting, and sustaining.
Includes bibliographical references and index.
Machine generated contents note: Introduction: Enter the Sanctuary1 Reconciling, Multiethnic, and Missional2 Moving the Church Beyond Crisis, Captivity, and Comfort3 Compassion, Mercy, and Justice4 Race5 The Gift of the Black Church6 Creating a Post-White Church7 Leadership8 The Beloved Life and Leadership Project9 Starting, Shifting, and SustainingNotesIndex.
Keywords: Church and minorities; Social integration -- Religious aspects -- Christianity; Reconciliation -- Religious aspects -- Christianity; Multiculturalism -- Religious aspects -- Christianity; Reconciliation - Religious aspects - Christianity; Church And Minorities; Multiculturalism - Religious aspects - Christianity; Social Integration - Religious Aspects - Christianity